Alcoholic solvent‐assisted ligand‐free room temperature Suzuki–Miyauracross‐coupling reaction. (25th May 2015) - Sarmah, Gayatri; Mondal, Manoj; Bora, Utpal
<x xml:space="preserve">Abstract</x> We have observed the enhancing effect of alcoholic solvents in palladium‐catalysed ligand‐free Suzuki–Miyaura reactions. No extra additives or ligands are required for the Suzuki–Miyaura reaction of aryl bromides with arylboronic acids when we carried out the reaction in alcoholic or aqueous alcoholic solvents. Moreover, ethanol or aqueous ethanol is found to be a very good solvent for the Suzuki–Miyaura reaction involving electronically diverse aryl bromides and arylboronic acids under mild and ligand‐free conditions with low catalyst loading. It is observed from Hg(0) poisoning tests that the in situ generated palladium(0) species is the actual catalytic species for the reaction. Copyright © 2015 John Wiley & Sons, Ltd.